Thermoplastic composition and use of additives

CN122804027APending Publication Date: 2026-09-22UPM KYMMENE OYJ
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202480088110.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-20
Publication Date
2026-09-22

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

Thermoplastic compositions prepared from at least one polymer, a lignin-based filler, and an additive are disclosed. Also disclosed is the use of the additive in the production of the thermoplastic compositions for increasing the impact strength values of the thermoplastic compositions. In addition, an article and the use of the thermoplastic compositions are disclosed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to a thermoplastic composition. Furthermore, this disclosure relates to the use of additives in the production process of the thermoplastic composition to improve its impact strength value. This disclosure also relates to an article and the use of the thermoplastic composition. Background Technology

[0002] Sustainability of all components in plastics production is crucial, and bio-based and renewable components are essential in plastics. Therefore, the inventors recognized the ongoing need to find sustainable solutions to produce thermoplastic compositions with increased amounts of renewable components for a wide range of applications. Summary of the Invention

[0003] This invention discloses a thermoplastic composition prepared from at least one polymer, a lignin-based filler, and an additive, wherein the additive is a modified siloxane, an amphiphilic copolymer, zinc stearate, or a combination or mixture of at least two of the above substances, and wherein: - The total amount of lignin-based filler used in the thermoplastic composition is 7.5-65% by weight. - The total amount of additives used in the thermoplastic composition is 0.1-10% by weight, and - The impact strength value of the thermoplastic composition is at least 10% higher than that of the corresponding thermoplastic composition. The corresponding thermoplastic composition is prepared in a similar manner to the thermoplastic composition, but without the use of additives.

[0004] The present invention also discloses the use of an additive together with at least one polymer and a lignin-based filler in the production of a thermoplastic composition, wherein the additive is a modified siloxane, an amphiphilic copolymer, zinc stearate, or a combination or mixture of at least two of the above substances, for increasing the impact strength value of the thermoplastic composition by at least 10% compared with that of a corresponding thermoplastic composition, wherein the corresponding thermoplastic composition is prepared in a similar manner to the thermoplastic composition, but without the use of the additive.

[0005] The present invention also discloses an article comprising a thermoplastic composition as defined in this specification.

[0006] This invention also discloses the use of the thermoplastic compositions defined in this specification in packaging, shells, automotive parts, aerospace parts, marine parts, machine parts, sporting equipment, sporting equipment parts, leisure equipment, leisure equipment parts, tools, tool parts, pipes, membranes, tubing, joints, bottles, films, bags, sacks, textiles, ropes, containers, storage tanks, electrical components, electronic components, power generation components, toys, electrical appliances, kitchenware, tableware, flooring, fabrics, medical applications, food contact materials, building materials, drinking water applications, and / or furniture. Detailed Implementation

[0007] This disclosure relates to a thermoplastic composition prepared from at least one polymer, a lignin-based filler, and an additive, wherein the additive is a modified siloxane, an amphiphilic copolymer, zinc stearate, or a combination or mixture of at least two of the above substances, and wherein: - The total amount of lignin-based filler used in the thermoplastic composition is 7.5-65% by weight; - The total amount of additives used in the thermoplastic composition is 0.1-10% by weight; and - The impact strength value of the thermoplastic composition is at least 10% higher than that of the corresponding thermoplastic composition. The corresponding thermoplastic composition is prepared in a similar manner to the thermoplastic composition, but without the use of additives.

[0008] This disclosure also relates to the use of an additive, together with at least one polymer and a lignin-based filler, in the production of a thermoplastic composition, wherein the additive is a modified siloxane, an amphiphilic copolymer, zinc stearate, or a combination or mixture of at least two of the above substances, for increasing the impact strength value of the thermoplastic composition by at least 10% compared to the impact strength value of a corresponding thermoplastic composition, wherein the corresponding thermoplastic composition is prepared in a similar manner to the thermoplastic composition, but without the use of the additive.

[0009] Therefore, the corresponding thermoplastic composition is prepared in a similar manner to the thermoplastic composition, except that no additives are used. The amount of additives used in preparing the thermoplastic composition is replaced in the corresponding thermoplastic composition by a corresponding additional amount of polymer. The corresponding thermoplastic composition is a reference thermoplastic composition. The corresponding thermoplastic composition is prepared in a similar manner to the thermoplastic composition disclosed in this specification, except that no additives are added. The amount of additives used in the thermoplastic composition disclosed in this specification is replaced by an equal amount of the polymer used. The total amount of lignin-based filler in the thermoplastic composition disclosed in this specification and the corresponding thermoplastic composition remains the same. In fact, except that the amount of additives is replaced by a corresponding additional amount of the polymer used, all other components and their amounts in the corresponding thermoplastic composition remain the same.

[0010] This disclosure also relates to an article comprising a thermoplastic composition as defined herein. In one embodiment, the thermoplastic composition is shaped into an article by extrusion, injection molding, compression molding, blow molding, injection blow molding, injection stretch blow molding, thermoforming, vacuum forming, melt spinning, electrospinning, melt blow molding, film blow molding, film casting, extrusion coating, rotational molding, co-extrusion, lamination, calendering, fused deposition modeling, or any combination thereof.

[0011] This disclosure further relates to the use of the thermoplastic compositions as defined in this specification in packaging, housings, automotive parts, aerospace parts, marine parts, machine parts, sporting equipment, sporting equipment parts, leisure equipment, leisure equipment parts, tools, tool parts, pipes, membranes, tubing, joints, bottles, films, bags, sacks, textiles, ropes, containers, storage tanks, electrical components, electronic components, power generation components, toys, appliances, kitchenware, tableware, flooring, fabrics, medical applications, food contact materials, building materials, drinking water applications, and / or furniture.

[0012] Thermoplastic compositions, also known as thermoplastic compositions, are plastic polymer materials that become soft or malleable at a certain elevated temperature and solidify upon cooling.

[0013] The additives used to prepare thermoplastic compositions are modified siloxanes, amphiphilic copolymers, zinc stearate, or combinations or mixtures of at least two of these substances.

[0014] Modified siloxanes refer to polysiloxanes whose main chain is organically modified with organic groups or organic side chains, and / or whose end groups are organically modified with organic groups or organic chains. In one embodiment, the additive is a modified siloxane. In one embodiment, the modified siloxane is an organically modified siloxane. In one embodiment, the modified siloxane is a polyester-modified siloxane.

[0015] In one embodiment, the additive is an amphiphilic copolymer. An amphiphilic polymer is a macromolecule containing both a hydrophobic and a hydrophilic component. Examples of hydrophobic components include polymethyl methacrylate, polymaleimide-methacrylate, polylactic acid, polypropylene oxide, polybutadiene, and polybutadiene succinate. Examples of hydrophilic components include polyacrylic acid, polyhydroxyethyl methacrylate, polymethacrylic acid, poly(ethylene glycol methacrylate), polyethylene oxide, polymethyl methacrylate, and polyvinylpyrrolidone. Other hydrophobic and hydrophilic components may also be used.

[0016] In one embodiment, the additive is zinc stearate.

[0017] In one embodiment, the additive is a combination or mixture of modified siloxane, amphiphilic copolymer, and zinc stearate. In another embodiment, the additive is a combination or mixture of modified siloxane and amphiphilic copolymer. In yet another embodiment, the additive is a combination or mixture of modified siloxane and zinc stearate. In yet another embodiment, the additive is a combination or mixture of amphiphilic copolymer and zinc stearate.

[0018] Increasing the amount of lignin-based filler in thermoplastic compositions has the added benefit of obtaining materials with higher renewable content and lower carbon footprint. Increasing the amount of lignin-based filler in thermoplastic compositions can improve the stiffness of the composition, i.e., Young's modulus. However, a drawback is that the (notched) impact strength decreases with increasing total amount of lignin-based filler in the thermoplastic composition. The inventors unexpectedly discovered that, contrary to common expectations, when the additives disclosed herein are added to thermoplastic compositions, the stiffness of the composition increases as expected, but surprisingly, the (notched) impact strength does not decrease. Furthermore, adding the additives disclosed herein to lignin-based thermoplastic compositions has the added benefit of positively affecting their elongation at break. Therefore, the prepared thermoplastic compositions have the desired stiffness, while the increase in brittleness is limited.

[0019] Without being limited to any specific theory as to why the (notched) impact strength value increases when this additive is used, it can be assumed that this is due to the lignin-based filler being able to interact with the additive, thereby being better dispersed in the polymer used.

[0020] As described in this specification, the use of this additive has the added benefit of improving the elongation at break of the thermoplastic composition. Improved dispersibility can reduce the presence of large particles in the thermoplastic composition, thereby reducing the formation of defects or voids that would otherwise make the material more prone to fracture.

[0021] The total amount of lignin-based filler used in the thermoplastic composition can be 7.5-65% by weight, or 10-60% by weight, or 12-55% by weight, or 14-45% by weight, or 15-35% by weight. An additional benefit of using a higher total amount of lignin-based filler is that the renewable content of the thermoplastic composition can be increased. The inventors unexpectedly discovered that an additional benefit of using the additives disclosed in this specification during the production of the thermoplastic composition is that a higher content of lignin-based filler in the thermoplastic composition can be achieved without compromising the performance of the resulting thermoplastic composition. Therefore, thermoplastic compositions with a higher lignin-based filler content can be produced. Thus, using the additives disclosed in this specification, thermoplastic compositions with a high content of renewable materials, an improved carbon footprint, and the mechanical properties required for subsequent applications can be produced.

[0022] In one embodiment, the total amount of additives used in the thermoplastic composition is 0.1-10% by weight, or 0.5-8% by weight, or 1-6% by weight, or 2-5.5% by weight, or 2.5-5% by weight. The inventors unexpectedly noted that the desired effect of increasing impact strength and notched impact strength can be achieved using only small amounts of the additives disclosed in this specification.

[0023] The total amount of polymer used in the thermoplastic composition may be 25-92.4% by weight, or 40-80% by weight, or 50-75% by weight.

[0024] In one embodiment, the impact strength value of the thermoplastic composition is at least 10%, or at least 15%, or at least 20%, or at least 30%, or at least 45% higher than that of a corresponding thermoplastic composition. In another embodiment, the impact strength value of the thermoplastic composition is 10%-500%, or 15%-400%, or 20%-350% higher than that of a corresponding thermoplastic composition.

[0025] In one embodiment, the additive is used to increase the impact strength value of the thermoplastic composition by at least 10%, or at least 15%, or at least 20%, or at least 30%, or at least 45% compared to the impact strength value of the corresponding thermoplastic composition. In another embodiment, the additive is used to increase the impact strength value of the thermoplastic composition by 10%-500%, 15%-400%, or 20%-350% compared to the impact strength value of the corresponding thermoplastic composition.

[0026] The impact strength of the thermoplastic composition can be determined by Charpy impact test according to ISO 179-1:2023.

[0027] In one embodiment, the notched impact strength of the thermoplastic composition is at least 5%, at least 7.5%, or at least 10% higher than that of the corresponding thermoplastic composition. In another embodiment, the notched impact strength of the thermoplastic composition is 5%-350%, 7.5%-300%, or 10%-250% higher than that of the corresponding thermoplastic composition.

[0028] In one embodiment, the additive is used to increase the notched impact strength of the thermoplastic composition by at least 5%, at least 7.5%, or at least 10% compared to the notched impact strength of a corresponding thermoplastic composition. In another embodiment, the additive is used to increase the notched impact strength of the thermoplastic composition by 5%-350%, 7.5%-300%, or 10%-250% compared to the notched impact strength of a corresponding thermoplastic composition.

[0029] The notched impact strength of thermoplastic compositions can be determined by Charpy impact test (notched specimen) according to ISO 179-1:2023.

[0030] Compatibilizers may also be used in the preparation of thermoplastic compositions. The compatibilizer may be a maleic anhydride graft polymer, a maleic anhydride copolymer, a glycidyl methacrylate graft polymer, a glycidyl methacrylate copolymer, or a combination or mixture of at least two of these compatibilizers. The total amount of compatibilizer in the thermoplastic composition may be 0.1-10% by weight. Using the above-mentioned compatibilizers in the production of thermoplastic compositions has the additional benefit of increasing the yield strength and / or yield strain values ​​of the thermoplastic compositions. The yield strength of the thermoplastic composition can be determined according to DIN EN ISO 527-2:2012. The yield strain value of the thermoplastic composition can be determined according to DIN EN ISO 527-2:2012.

[0031] In one embodiment, the polymer is polyethylene, polypropylene, polystyrene, ethylene-vinyl acetate copolymer (EVA), polybutylene adipate-terephthalate copolymer (PBAT), polyamide, polyacrylate, polyester, acrylonitrile-butadiene-styrene copolymer (ABS), polycarbonate, polylactic acid (PLA), polyvinyl chloride (PVC), styrene-ethylene-butene-styrene copolymer (SEBS), styrene-butadiene-styrene copolymer (SBS), or any combination or mixture thereof. That is, the thermoplastic composition can be produced using one type of polymer, or a combination of two or more different polymers can be used.

[0032] The polymers used in the thermoplastic composition may be derived from (a) a fossil source. At least one polymer may be derived from (a) a bio-based source. The at least one polymer may be derived from either a fossil source or a bio-based source. All polymers used in the thermoplastic composition may be derived from either a fossil source or a bio-based source. Alternatively, polymers from both fossil and bio-based sources may be used in the thermoplastic composition. Furthermore, a mixture of polymers from both fossil and bio-based sources may also be used in the thermoplastic composition.

[0033] In one embodiment, the lignin-based filler is hydrothermally carbonized lignin. The lignin-based filler is prepared from hydrothermally carbonized (HTC) lignin. In one embodiment, the lignin-based filler comprises or is composed of hydrothermally carbonized lignin.

[0034] Therefore, the fillers used to prepare thermoplastic compositions are lignin-based fillers prepared from lignin that has undergone hydrothermal carbonization (HTC). Hydrothermal carbonization of lignin refers to the thermochemical transformation of lignin-containing materials in an aqueous suspension. Hydrothermal carbonization of lignin produces lignin derivatives with high carbon content and functional groups.

[0035] Lignin is a biopolymer and a key structural material in the supporting tissues of most living plants. It is a renewable material that can be used in a variety of applications.

[0036] Lignin can be derived from any suitable source. For example, lignin can be derived from wood, such as hardwood, softwood, broadleaf wood, or combinations thereof, or from any other biomass, such as sugarcane. Wood can be derived from, for example, pine, poplar, beech, aspen, spruce, eucalyptus, ash, or birch. Wood can also be any combination or mixture of these woods.

[0037] In one embodiment, the lignin-based filler is prepared from lignin derived from enzymatic hydrolysis and / or sulfate pulping and subjected to hydrothermal carbonization. In another embodiment, the lignin-based filler is prepared from lignin derived from enzymatic hydrolysis and subjected to hydrothermal carbonization. In yet another embodiment, the lignin-based filler is prepared from lignin derived from sulfate pulping and subjected to hydrothermal carbonization.

[0038] In one embodiment, the enzymatic hydrolysis method involves enzymatically hydrolyzing a plant-based raw material (e.g., woody material). Prior to enzymatic hydrolysis, the woody material may undergo pretreatment, which may include impregnation and partial hydrolysis before enzymatic hydrolysis. Pretreatment can extract cellulose from the woody material, which can then be hydrolyzed in the enzymatic hydrolysis process.

[0039] In one embodiment, the enzymatic hydrolysis method includes enzymatically hydrolyzing cellulose. In one embodiment, the lignin-based filler is prepared from lignin produced during wood pulping (e.g., sulfate pulping lignin).

[0040] The preparation method of lignin-based filler is described below. The lignin used can be derived, for example, from a method in which lignin is formed during the enzymatic hydrolysis of lignocellulose raw materials, or from a sulfate pulping method. Other lignin sources may also be used.

[0041] In one embodiment, the starting material for preparing the lignin-based filler is lignin derived from enzymatic hydrolysis. Enzymatic hydrolysis is a process in which chemical bonds in molecules are broken with the assistance of enzymes in the presence of water. In one embodiment, enzymatic hydrolysis includes the enzymatic hydrolysis of cellulose. In another embodiment, the lignin-based filler is prepared from lignin derived from enzymatic hydrolysis and subjected to hydrothermal carbonization.

[0042] The inventors unexpectedly discovered that when lignin derived, for example, from enzymatic hydrolysis, is used to produce lignin-based fillers, the ash content of the lignin-based fillers can be reduced. Lower ash content also has the added benefit of, for example, higher purity of the lignin-based fillers.

[0043] Lignin can be derived from second-generation biomass. Second-generation (2G) biomass can refer to non-edible and non-food biomass. In contrast to the term second-generation biomass, first-generation biomass should refer to edible biomass.

[0044] The derived lignin is soluble in alkaline solutions such as NaOH. Dissolution can be achieved by heating the mixture of lignin and alkaline solution to approximately 80°C, adjusting the pH to above 7 (e.g., 9-11), and mixing the mixture for a predetermined time. The mixing time can last approximately 2-3 hours. The specific pH value depends on the target grade of the product.

[0045] The dissolved lignin can then undergo hydrothermal carbonization (HTC).

[0046] Hydrothermal carbonization can be carried out in a reactor (HTC reactor) or, as needed, in batches in multiple parallel reactors. The dissolved lignin can be preheated before entering the HTC reactor. The temperature inside the HTC reactor can be 150-250°C, and the pressure can be 20-30 bar. The residence time in the HTC reactor can be approximately 3-6 hours. In the HTC reactor, the lignin is carbonized, thereby precipitating stable lignin derivatives with a high specific surface area. The resulting slurry containing carbonized lignin can then be removed and cooled.

[0047] Therefore, a slurry containing lignin-based fillers is formed.

[0048] The slurry containing lignin-based filler can be fed into a separation unit, where precipitated lignin can be separated from the slurry. The separated lignin-based filler can be dried and recycled. If necessary, the lignin-based filler can be washed before drying. The recycled lignin-based filler can be further processed before use as a lignin-based filler, such as crushing, further drying, and grinding. The resulting lignin-based filler is a renewable bio-based filler.

[0049] In the process described above, the lignin polymers are interconnected. Therefore, the lignin-based packing material can be considered to contain or consist of interconnected lignin polymers. The interconnected or linked lignin polymers may no longer dissolve. However, smaller lignin polymer chains remain soluble and can therefore be analyzed using standard analytical techniques such as size exclusion chromatography or nuclear magnetic resonance spectroscopy (NMR spectroscopy), which require the analyte to be dissolved in a solvent. Thus, the different properties of the soluble portions of the lignin-based packing material can be determined.

[0050] Lignin-based fillers may contain 0.1-3% by weight, or 0.1-2.5% by weight, or 0.2-2.0% by weight, or 0.3-1.5% by weight, or 0.4-1.0% by weight of total ash. The ash content can be determined according to DIN 51719. The inventors unexpectedly discovered that, for example, when using lignin prepared by enzymatic hydrolysis to produce lignin-based fillers, the ash content of the lignin-based fillers can be reduced. Lower ash content has additional benefits, such as higher purity of the lignin-based fillers.

[0051] Lignin-based fillers may contain 62-70% by weight, or 63-69% by weight, or 64-68% by weight of total carbon. The carbon content in lignin-based fillers can be determined according to DIN 51732 (1997) standard.

[0052] The solubility of lignin-based fillers in 0.1 M NaOH can be 1-40% by weight, 3-35% by weight, or 5-30% by weight. Solubility can be determined as follows: First, dry the sample at 60°C for 4 hours. Weigh 0.5 g of the sample and suspend it in 50 mL of 1% 0.1 M NaOH at 22°C. After mixing for another hour, place the sample on 1.6 μm glass microfiber filter paper and dry the filter paper along with the sample at 60°C for 2 hours. The dissolved sample fraction can be determined by gravimetric analysis.

[0053] When the soluble fraction of the lignin-based filler is determined, the lignin-based filler may have a weight-average molecular weight (Mw) of 1000-4000 Da, 1300-3700 Da, 1700-3200 Da, 2500-3000 Da, 2600-2900 Da, or 2650-2850 Da. The weight-average molecular weight can be determined by size exclusion chromatography (SEC) using 0.1 M NaOH as the eluent, with a sample volume of approximately 1 mg / ml dissolved in 0.1 M NaOH. Polystyrene sulfonate standards are used for molecular weight determination. A UV detector with a wavelength of 280 nm is used.

[0054] When the determination is based on the soluble fraction of lignin-based fillers, the polydispersity index (PDI) of the lignin-based fillers can be 1.5-5.0, 1.8-4.5, 1.9-4.3, 2.1-4.0, 2.4-3.5, or 2.6-3.2. The polydispersity index can be determined by size exclusion chromatography (SEC). PDI is an indicator of the molecular weight distribution in a given polymer sample. PDI is calculated by dividing the weight-average molecular weight (Mw) by the number-average molecular weight (Mn). PDI reflects the distribution of molecular weights in a batch of polymers.

[0055] This lignin-based filler can have a specific surface area (STSA) value of 3-150 m² / g, 5-100 m² / g, or 7-60 m² / g. The STSA value can be determined according to ASTM D6556 standard.

[0056] The lignin-based filler may have a density of up to 1.5 g / cm³. In one embodiment, the density of the lignin-based filler is 1.0-1.5 g / cm³, 1.15-1.35 g / cm³, or 1.1-1.4 g / cm³. The density can be determined according to ISO 21687 standard.

[0057] Thermoplastic compositions can be prepared using at least one polymer, a lignin-based filler, and an additive. Other components or materials, such as plasticizers, compatibilizers, lubricants, stabilizers, antioxidants, curing agents, foaming agents, etc., can also be used to prepare thermoplastic compositions. In one embodiment, combining the at least one polymer, the lignin-based filler, and the additive further includes combining one or more plasticizers, compatibilizers, lubricants, stabilizers, antioxidants, curing agents, and / or foaming agents to form a thermoplastic composition.

[0058] When preparing thermoplastic compositions, a so-called masterbatch may first be prepared using at least the aforementioned polymer, lignin-based filler, and additives. The masterbatch can be prepared by mixing the polymer, lignin-based filler, and additives at elevated temperatures. Furthermore, other plasticizers, compatibilizers, lubricants, stabilizers, antioxidants, curing agents, foaming agents, etc., may be included in the masterbatch as needed. Other fillers may be used in addition to lignin-based fillers. The total amount of other fillers can be 0.1-60% by weight. Therefore, they can be used in combination with other fillers in various proportions. Talc, chalk, carbon black or other pigments, polymer fibers, natural fibers, bio-based fibers, and glass fibers are all examples of such other fillers. A masterbatch is generally considered a solid product (typically a plastic, rubber, or elastomer) in which pigments or fillers are optimally dispersed in a carrier material at high concentrations. The carrier material is compatible with the main polymer to be mixed with during compounding or subsequent molding, thereby giving the final plastic product (i.e., the thermoplastic composition) the color or properties derived from the masterbatch.

[0059] Alternatively, the thermoplastic composition can be directly compounded from the polymer, lignin-based filler, and additives at elevated temperatures. Furthermore, other compatibilizers, lubricants, stabilizers, antioxidants, curing agents, foaming agents, and other fillers (as needed) can also be directly compounded with the polymer, lignin-based filler, and additives. Alternatively, they can be compounded with the polymer, lignin-based filler, and additives to form a masterbatch.

[0060] However, in one embodiment, no fillers other than lignin-based fillers are used when preparing the thermoplastic composition.

[0061] The temperature used when mixing the components may vary depending on the type of polymer used. Those skilled in the art can readily obtain the applicable temperature for each polymer. Furthermore, polymer suppliers define suitable processing temperatures for different polymers. Typically, usable temperatures are, for example, 20-350 °C, 40-330 °C, 70-300 °C, 120-280 °C, or 150-260 °C.

[0062] Some components in a thermoplastic composition may be cured at elevated temperatures during the mixing process.

[0063] Thermoplastic compositions can be either non-expanded or expanded. When a thermoplastic composition is expanded, it can take the form of a foam. Expanded thermoplastic compositions can be formed by introducing air or gas (such as carbon dioxide) bubbles into the thermoplastic composition during the preparation process. For example, a foaming agent can be used to expand the thermoplastic composition to make it foam. Polymer foaming refers to the process of introducing gas-filled cells (bubbles) into the material structure. By foaming, the density of the material can be reduced, thus reducing material consumption. Furthermore, the density of the foam can be controlled, and a wide range of densities can be obtained according to product requirements. This helps to reduce weight and lower material costs. Such expanded thermoplastic compositions can also be called foamed thermoplastic compositions or polymer foams.

[0064] The thermoplastic composition can be molded into articles by extrusion, injection molding, compression molding, blow molding, injection blow molding, injection stretch blow molding, thermoforming, vacuum forming, melt spinning, electrospinning, meltblowing, blown film, film casting, extrusion coating, rotational molding, co-extrusion, lamination, calendering, fused deposition modeling, or any combination of the above methods.

[0065] The total organic carbon content of the thermoplastic composition can be determined to be 4%-100% according to DIN EN 15936:2012-11. The term "total organic carbon (TOC)" can be understood as the carbon content of organic compounds or, in this case, the thermoplastic composition.

[0066] The content of renewable materials in the thermoplastic composition may be at least 7.5% by weight, or at least 10% by weight, or at least 15% by weight, or at least 20% by weight.

[0067] The additional benefit of using the additives disclosed in this specification in thermoplastic compositions is that the stiffness of the thermoplastic composition is increased while ensuring that the impact strength value or notched impact strength value does not drop to an unsuitable level.

[0068] The additional benefit of using the additives disclosed in this specification in the production of thermoplastic compositions is that it allows for the use of higher amounts of lignin-based fillers in the thermoplastic compositions without compromising the mechanical properties of the resulting thermoplastic compositions.

[0069] The additional benefit of the thermoplastic compositions disclosed in this specification is that they have a high proportion of renewable materials and an improved carbon footprint, while also possessing the mechanical properties required for the subsequent use of thermoplastic compositions.

[0070] Example

[0071] The implementation plan described below will be explained in detail.

[0072] The following description discloses several embodiments in detail so that those skilled in the art can utilize the methods based on this disclosure. This specification does not discuss all the steps of the embodiments in detail, as some steps are obvious to those skilled in the art based on this specification.

[0073] Example 1 - Preparation of thermoplastic composition

[0074] In this embodiment, different thermoplastic compositions were prepared using different amounts of lignin-based filler (LBF) (prepared from hydrothermally carbonized lignin). Different additives used to prepare the thermoplastic compositions of the test examples were tested. The preparation methods of the corresponding thermoplastic compositions were substantially the same as those of the thermoplastic compositions of the examples, but without the addition of any additives. In the corresponding thermoplastic compositions, additional amounts of polymer were used to replace the additives used in the thermoplastic compositions of the examples. Furthermore, comparative examples were prepared using maleic anhydride-grafted polypropylene (PP-g-MAH). The polymer used in all compositions was polypropylene (PP). Tables 1 and 2 list the prepared compositions: Table 1. Thermoplastic compositions prepared using 15% by weight lignin-based filler

[0075] Polypropylene (PP): Moplen HP501L (Lyondellbasell)

[0076] Amphiphilic copolymer: Tegomer P121 (Evonik)

[0077] Maleic anhydride-grafted polypropylene (PP-g-MAH): Licocene PPMA7452 GR (Clariant)

[0078] Zinc stearate: Zincum TX (Baerlocher)

[0079] Amphiphilic copolymer: Tegomer P121 (Evonik)

[0080] Modified siloxane: Tegomer H-Si 6441 P (Evonik, a polyester-modified siloxane)

[0081] Table 2. Thermoplastic compositions prepared using 30% by weight lignin-based filler

[0082] The properties of the prepared thermoplastic composition were tested as follows: Impact strength values ​​were measured according to ISO 179-1:2023 standard. Notched impact strength values ​​were measured according to ISO 179-1:2023 standard. The elongation at break was measured according to the DIN EN ISO 527-2:2012 standard. The measured values ​​are listed in Table 3. The measured values ​​of the thermoplastic compositions of the examples and the comparative examples were compared with the measured values ​​of the corresponding thermoplastic compositions to calculate the numerical changes relative to the corresponding thermoplastic compositions (Table 4).

[0083] The measurement and calculation results are shown in Tables 3 and 4 below: Table 3. Measured values ​​of the prepared thermoplastic compositions

[0084] Table 4. Calculated value changes of the prepared thermoplastic compositions

[0085] As can be seen from the table above, the use of additives as disclosed in this disclosure significantly improves the impact strength and notched impact strength of the thermoplastic composition.

[0086] It will be apparent to those skilled in the art that the basic idea can be implemented in various ways as technology advances. Therefore, the implementation schemes are not limited to the embodiments described above; rather, they may vary within the scope of the claims.

[0087] The embodiments described herein can be used in any combination with each other. Multiple embodiments can be combined together to form another embodiment. The thermoplastic compositions, articles, and uses disclosed herein may include at least one of the above embodiments. It should be understood that the above advantages and benefits may relate to one embodiment or multiple embodiments. The embodiments are not limited to those that solve any or all of the described problems or have any or all of the described advantages and benefits. Furthermore, it should be understood that "an" item refers to one or more of these items. The term "comprising" as used in this specification means including the feature or behavior that follows, but does not exclude the presence of one or more additional features or behaviors.

Claims

1. A thermoplastic composition prepared from at least one polymer, a lignin-based filler, and an additive, wherein the additive is a modified siloxane, an amphiphilic copolymer, zinc stearate, or a combination or mixture of at least two of the above substances, and wherein: - The total amount of lignin-based filler used in the thermoplastic composition is 7.5-65% by weight. - The total amount of additives used in the thermoplastic composition is 0.1-10% by weight, and - The impact strength value of the thermoplastic composition is at least 10% higher than that of the corresponding thermoplastic composition. The corresponding thermoplastic composition is prepared in a similar manner to the thermoplastic composition, but without the use of additives.

2. The thermoplastic composition according to claim 1, wherein the elongation at break of the thermoplastic composition is at least 15%, at least 30%, at least 45%, or at least 60% higher than the elongation at break of the corresponding thermoplastic composition.

3. The thermoplastic composition according to any one of the preceding claims, wherein the total amount of lignin-based filler used in the thermoplastic composition is 10-60% by weight, 12-55% by weight, 14-45% by weight, or 15-35% by weight.

4. The thermoplastic composition according to any one of the preceding claims, wherein the total amount of additives used in the thermoplastic composition is 0.5-8% by weight, 1-6% by weight, 2-5.5% by weight, or 2.5-5% by weight.

5. The thermoplastic composition according to any one of the preceding claims, wherein the impact strength value of the thermoplastic composition is at least 10%, at least 15%, at least 20%, at least 30%, or at least 45% higher than the impact strength value of the corresponding thermoplastic composition.

6. The thermoplastic composition according to any one of the preceding claims, wherein the notched impact strength value of the thermoplastic composition is at least 5%, at least 7.5%, or at least 10% higher than the notched impact strength value of the corresponding thermoplastic composition.

7. The thermoplastic composition according to any one of the preceding claims, wherein the polymer is polyethylene, polypropylene, polystyrene, ethylene-vinyl acetate copolymer (EVA), polybutylene adipate-terephthalate copolymer (PBAT), polyamide, polyacrylate, polyester, acrylonitrile-butadiene-styrene copolymer (ABS), polycarbonate, polylactic acid (PLA), polyvinyl chloride (PVC), styrene-ethylene-butene-styrene copolymer (SEBS), styrene-butadiene-styrene copolymer (SBS), or any combination or mixture thereof.

8. The thermoplastic composition according to any one of the preceding claims, wherein the lignin-based filler is lignin that has undergone hydrothermal carbonization.

9. Use of an additive in conjunction with at least one polymer and a lignin-based filler in the production of a thermoplastic composition, wherein the additive is a modified siloxane, an amphiphilic copolymer, zinc stearate, or a combination or mixture of at least two of the above substances, for increasing the impact strength value of the thermoplastic composition by at least 10% compared to the impact strength value of a corresponding thermoplastic composition, wherein the corresponding thermoplastic composition is prepared in a similar manner to the thermoplastic composition, but without the use of the additive.

10. The use according to claim 9, for increasing the elongation at break of the thermoplastic composition by at least 15%, at least 30%, at least 45%, or at least 60% compared to the elongation at break of the corresponding thermoplastic composition.

11. The use according to any one of claims 9 to 10, wherein the total amount of lignin-based filler used in the thermoplastic composition is 7.5-65% by weight, 10-60% by weight, 12-55% by weight, 14-45% by weight, or 15-35% by weight.

12. The use according to any one of claims 9 to 11, wherein the total amount of additives used in the thermoplastic composition is 0.1-10% by weight, 0.5-8% by weight, 1-6% by weight, 2-5.5% by weight, or 2.5-5% by weight.

13. The use according to any one of claims 9 to 12, for increasing the impact strength value of the thermoplastic composition by at least 10%, at least 15%, at least 20%, at least 30%, or at least 45% compared to the impact strength value of the corresponding thermoplastic composition.

14. The use according to any one of claims 9 to 13, for increasing the notched impact strength value of the thermoplastic composition by at least 5%, at least 7.5%, or at least 10% compared to the notched impact strength value of the corresponding thermoplastic composition.

15. The use according to any one of claims 9 to 14, wherein the polymer is polyethylene, polypropylene, polystyrene, ethylene-vinyl acetate copolymer (EVA), polybutylene adipate-terephthalate copolymer (PBAT), polyamide, polyacrylate, polyester, acrylonitrile-butadiene-styrene copolymer (ABS), polycarbonate, polylactic acid (PLA), polyvinyl chloride (PVC), styrene-ethylene-butene-styrene copolymer (SEBS), styrene-butadiene-styrene copolymer (SBS), or any combination or mixture thereof.

16. The use according to any one of claims 9 to 15, wherein the lignin-based filler is lignin treated with hydrothermal carbonization.

17. An article comprising the thermoplastic composition according to any one of claims 1 to 8.

18. The article of claim 17, wherein the thermoplastic composition is formed into an article by extrusion, injection molding, compression molding, blow molding, injection blow molding, injection stretch blow molding, thermoforming, vacuum forming, melt spinning, electrospinning, melt blow molding, film blow molding, film casting, extrusion coating, rotational molding, co-extrusion, lamination, calendering, fused deposition modeling, or any combination thereof.

19. Use of the thermoplastic composition of any one of claims 1 to 8 in packaging, housings, automotive parts, aerospace parts, marine parts, machine parts, sporting equipment, sporting equipment parts, leisure equipment, leisure equipment parts, tools, tool parts, pipes, membranes, tubing, joints, bottles, films, bags, sacks, textiles, ropes, containers, storage tanks, electrical components, electronic components, power generation components, toys, electrical appliances, kitchenware, tableware, flooring, fabrics, medical applications, food contact materials, building materials, drinking water applications, and / or furniture.